Systemic metabolic changes in acute and chronic lymphocytic choriomeningitis virus infection - Caroline R. Bartman; Shengqi Hou; Fabian Correa; Yihui Shen; Victoria da Silva-Diz; Maya Aleksandrova; Daniel Herranz; Joshua D. Rabinowitz; Andrew M. Intlekofer (Molecular Metabolism)
Objective: Viral infection of cells leads to metabolic changes, but how viral infection changes whole-body and tissue metabolism in vivo has not been comprehensively studied. In particular, it is unknown how metabolism might be differentially affected by an acute infection that the immune system can successfully clear compared to a chronic persistent infection. Methods: Here we used metabolomics and isotope tracing to identify metabolic changes in mice infected with acute or chronic forms of lymphocytic choriomeningitis virus (LCMV) for three or eight days. Results: Both types of infection alter metabolite levels in blood and tissues, including itaconate and thymidine. However, we observed more dramatic metabolite changes in the blood and tissues of mice with persisting LCMV infection compared to those infected with the acute viral strain. Isotope tracing revealed that the contribution of both glucose and glutamine to the tricarboxylic acid (TCA) cycle increase in the spleen, liver, and kidneys of mice infected with chronic LCMV, while acute LCMV only increases the contribution of glutamine to the TCA cycle in the spleen. We found that whole-body turnover of both glutamine and thymidine increase during acute and chronic infection, whereas whole-body glucose turnover surprisingly does not change. Activated T cells in vitro produce thymidine and virus-specific T cells ex vivo have increased thymidine levels, nominating T lymphocytes as the source of thymidine in LCMV infection. Conclusions: In sum, we provide comprehensive measurements of whole-body and tissue metabolism in acute and chronic viral infection, and identify altered thymidine metabolism as a marker of viral infection.